Análises sinérgicas microbianas de linhagens selecionadas para a biodegradação do herbicida Amicarbazone e testes com cana-de-açúcar - Siqueira, Beatriz Zanata (Universidade Federal de São Carlos, 2023)
Agriculture plays a significant role in our country's economy, but it generates substantial environmental impacts due to the excessive use of pesticides. The pursuit of increased agricultural production often overlooks these impacts, harming soil microbiota and prompting the search for techniques to mitigate the damage. The research aimed to assess the use of microbial strains in the bioremediation of agricultural soil contaminated with the herbicide amicarbazone, commonly used in sugarcane cultivation (Saccharum officinarum). Additionally, it sought to examine the influence of these strains on the productivity of the studied species. Respirometry assays were conducted to verify the viability of soil microbiota in degrading the herbicide. Subsequently, the isolated strains underwent colorimetric tests using the redox indicator 2,6-dichlorophenol-indophenol (DCPIP), which measures catabolic activity in pollutant degradation. Inoculation tests of the strains in sugarcane cultivation soil were also performed, emphasizing the complex interactions among soil microorganisms, herbicides, and plant growth. This included testing the relationship between the studied pesticide and purple morning glory (Ipomoea purpurea). Based on the respirometric tests, it was observed that the soil microbiota had the potential to degrade the herbicide, as evidenced by the difference in CO2 production between the control (176.24 mg) and the Herbicide 200mg/L Group (209.38 mg). In the colorimetric assay, selected yeasts were capable of degrading the herbicide, with the consortium of three microorganisms yielding the best result. When inoculated in the soil, it was observed that the interaction between microorganisms A and B notably inhibited sugarcane buds, while the treatment containing microorganism C showed positive growth, suggesting its limited efficiency in degrading the herbicide, as observed in the colorimetric assay. Regarding the test with the grass, it was evident that joint inoculation resulted in a significant increase in the final length of seedlings compared to treatments that received only the herbicide. In conclusion, it was determined that microorganisms have the capacity to degrade the herbicide, with strains A and B demonstrating higher efficacy. However, it is believed that the by-products of this degradation may be detrimental to sugarcane development, negatively impacting growth. Thus, the results highlight the potential of bioremediation studies in agriculture, illustrating the capability of the microbiota present in the environment.
Microbial synergistic analysis of selected strains for the biodegradation of the herbicide Amicarbazone and tests with sugar cane
Keywords: Agrotóxico; Biorremediação; Colorimetria; Ecotoxicidade; Respirometria; Pesticide; Bioremediation; Colorimetry; Ecotoxicity; Respirometry; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE::MICROBIOLOGIA AGRICOLA